2018
DOI: 10.1186/s13613-018-0379-5
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of response to fixed-dose vasopressin in adult patients with septic shock

Abstract: BackgroundVasopressin is often utilized for hemodynamic support in patients with septic shock. However, the most appropriate patient to initiate therapy in is unknown. This study was conducted to determine factors associated with hemodynamic response to fixed-dose vasopressin in patients with septic shock.MethodsSingle-center, retrospective cohort of patients receiving fixed-dose vasopressin for septic shock for at least 6 h with concomitant catecholamines in the medical, surgical, or neurosciences intensive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
104
0
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 63 publications
(111 citation statements)
references
References 35 publications
6
104
0
1
Order By: Relevance
“…The scenarios for which there are physiological bases for vasopressin use may represent opportunities for restrictions in the short‐term and research in the intermediate‐to‐long term. These areas included vasopressin use in patients with severe acidemia, low serum lactate concentration, vasopressin as initial monotherapy, and those at risk for renal failure …”
Section: Discussionmentioning
confidence: 99%
“…The scenarios for which there are physiological bases for vasopressin use may represent opportunities for restrictions in the short‐term and research in the intermediate‐to‐long term. These areas included vasopressin use in patients with severe acidemia, low serum lactate concentration, vasopressin as initial monotherapy, and those at risk for renal failure …”
Section: Discussionmentioning
confidence: 99%
“…These findings were corroborated in two subsequent studies yet appeared to be limited to patients who received AVP doses of 0.067 units/minute and those receiving CRRT . However, recent evaluations did not observe increased bilirubin concentrations after AVP initiation, even when doses up to 0.067 units/minute were studied . These discrepant findings suggest that monitoring for increased bilirubin concentration after AVP initiation is warranted, but baseline bilirubin concentration should not affect the decision to initiate AVP.…”
Section: Adverse Drug Reactions Of Avp and Risk Mitigationmentioning
confidence: 71%
“…However, in clinical studies, AVP was not associated with AKI or failure. In fact, recent clinical studies found that AVP may have positive effects on renal function and was shown to reduce the risk of progression of AKI and the need for continuous renal replacement therapy (CRRT) . However, these effects may be driven by a reduction in serum creatinine and increased urine output with AVP that may influence the decision to initiate CRRT.…”
Section: Adverse Drug Reactions Of Avp and Risk Mitigationmentioning
confidence: 99%
See 2 more Smart Citations